2017
DOI: 10.1093/aobpla/plx012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen and tiller type on grain yield and physiological responses in rice

Abstract: Tillering is an important agronomic trait for rice population quality and grain production. Nitrogen fertilizer application increased the number of rice tillers, but not every tiller contributes equally to the overall yield. Heterogeneity in tiller yield of rice increased with increasing nitrogen levels. Typically, late emerging tillers contributed less to the grain yield. Under high nitrogen conditions, most of the nutrients were retained in the straw of late emerging tillers; these tillers have high transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 35 publications
7
55
1
1
Order By: Relevance
“…N is a crucial macronutrient for plant development. Although previous studies have elucidated the regulatory mechanisms of the axillary bud growth under N stress [22,26,27,29,35,54], many regulators and their regulatory mechanisms are still unclear. This work revealed that the axillary bud growth rate was altered by different N concentrations, and integrated transcriptomic data from the basal parts and axillary buds of rice plants grown under different N concentrations via RNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“…N is a crucial macronutrient for plant development. Although previous studies have elucidated the regulatory mechanisms of the axillary bud growth under N stress [22,26,27,29,35,54], many regulators and their regulatory mechanisms are still unclear. This work revealed that the axillary bud growth rate was altered by different N concentrations, and integrated transcriptomic data from the basal parts and axillary buds of rice plants grown under different N concentrations via RNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“…N is a crucial macronutrient for plant development. Although previous studies have elucidated the regulatory mechanisms of the axillary bud growth under N stress [22,26,27,29,35,54], many regulators and their regulatory mechanisms are still unclear. This work revealed that the axillary bud growth rate was altered by different N concentrations, and integrated transcriptomic data from the basal parts and axillary buds of rice plants grown under different N concentrations via RNAseq.…”
Section: Discussionmentioning
confidence: 99%
“…N is a crucial macronutrient for plant development. Previous studies have elucidated the regulatory mechanisms of the axillary bud growth of plants grown under N stress [22,26,27,29,35,56]; however, many regulators and their regulatory mechanisms are still unclear. This work revealed that the growth rate of axillary buds was distinct in plants grown under different N concentrations, and integrated transcriptomic data from the basal parts and axillary buds of rice plants grown under six different N concentrations via RNA-sEq.…”
Section: Discussionmentioning
confidence: 99%